The Educational Curriculum to Prepare Scholars in Muhammad Natsir’s book Fiqhud Da'wah and Yusuf al-Qaradawi’s book Thaqafah Daiyah - Joko, Ganang Prihatmoko; Saeful Anwar; Akhmad Alim; Abas Mansur Tamam (Formosa Journal of Multidisciplinary Research, 2024)
Islamic higher education should ideally produce a generation proficient in religious knowledge and equipped with skills to navigate contemporary challenges. Unfortunately, the current perception of Islamic higher education is that it possesses low quality, particularly concerning graduates of Islamic studies programs who are considered less capable of keeping up with the pace of modern developments. Consequently, there is a need for a reconstruction of the education system, especially focusing on the curriculum as the foundation of learning, to ensure that educational objectives are achieved optimally. This research aims to examine the curriculum presented in two books: "Tsaqafah Daiyah" by Yusuf Qardhawy and "Fiqhud Dakwah" by Muhammad Natsir. The research methodology employed is qualitative, utilizing observational methods, interviews, document analysis, and directed discussion forums. The research findings conclude that both books can serve as references in formulating an ideal curriculum for educating scholars in higher education. This curriculum is expected to provide the basis for preparing scholar candidates at the undergraduate level with a comprehensive understanding and reinforcement of Islamic jurisprudence. This knowledge should be integrated with a deep understanding of practical insights and relevant materials to address various challenges faced by the community and the nation.